1993
DOI: 10.1055/s-2007-997955
|View full text |Cite
|
Sign up to set email alerts
|

Ballonokklusionstest der A. carotis interna zur Prüfung der Resektabilität bei gefäßinfiltrierender zervikaler Metastasierung vorangeschrittener Kopf-Hals-Karzinome - Heidelberger Erfahrungen

Abstract: During the last two years 17 patients of the ENT-Department of the University of Heidelberg suffering from squamous-cell carcinomas of the head and neck underwent a balloon occlusion test of the internal carotid artery (ICA). The investigation was performed because of tumorous infiltration of the large cervical vessels. The balloon occlusion of the ICA was accomplished at the Department of Neuroradiology of the University of Heidelberg. While stopping bloodflow in the ICA of one side for 15-20 min, clinical, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Experimental studies showed a correlation between reduced CBF and pathological changes in the SEPs [17]. In a clinical study of 17 patients, Dietz et al remarks that measurement of the SEPs should be preferred compared with HMPAO SPECT, as only these are correlated with the CBF [18].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed a correlation between reduced CBF and pathological changes in the SEPs [17]. In a clinical study of 17 patients, Dietz et al remarks that measurement of the SEPs should be preferred compared with HMPAO SPECT, as only these are correlated with the CBF [18].…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur werden verschiedene Methoden zur Abschätzung und Minimierung dieses Risikos beschrieben: manuelle Kompression der ACC (Matas-Test), die Hexamethyl-Propylenaminoxim-Single-Photonen-Emissions-Computertomographie (HMPAO-SPECT), die Karotisangiographie mit Probeokklusion sowie der "xenon-enhanced computed tomography cerebral blood flow" (Xe/CT CBF) [4,6,7,15,18,19].…”
unclassified